Triad of the Articulation Model of Integrated Management Systems [TAM - (HSEQ)] - Alvarado Rueda, René Alejandro; Pérez Gómez, Gonzalo Carlos José (TECCIENCIA, 2016)
Integrated Management Systems include Quality Management Systems (QMS), Environmental Management Systems (EMS), and Occupational Health and Safety Management Systems (OHSMS), which need a continuous and efficient improvement in companies. Many factors hinder achieving quality certifications in environment and occupational safety and health due to dislocation of the corresponding systems. This work aims to propose a model that contributes to the design and integration of these models. This is constructed by studies of unique cases in companies in Bogotá. It was also supported by surveys taking into account the requirements stated by standards such as ISO 9001: 2008, ISO 14001: 2004 and OHSAS 18001:2007. Meanwhile, it was supported with interviews to identify typical problems; and Recursion-Function Matrix between processes and functions. The Triad Model Articulation of Integrated Management Systems [TMA - (HSEQ)] is exposed and designed based on the corresponding standard. The standards OHSAS 18001: 2008 and ISO 14001:2004 are articulated by the norm ISO 9001: 2008 and articulated. This triad should investigate the use of ICT for Integrated Systems Management - (HSEQ) and consider approval of updating future versions of standards (ISO 9001: 2015, ISO 14001: 2015 and ISO 45001: 2016).